Circulating Angiotensin-(1–7) Is Reduced in Alzheimer’s Disease Patients and Correlates With White Matter Abnormalities: Results From a Pilot Study - Ribeiro, Victor Teatini; Cordeiro, Thiago Macedo e; Filha, Roberta da Silva; Perez, Lucas Giandoni; Caramelli, Paulo; Teixeira, Antônio Lúcio; de Souza, Leonardo Cruz; Simões e Silva, Ana Cristina (Frontiers in Neuroscience, 2021)
Introduction: Alzheimer’s disease (AD) is the leading cause of dementia worldwide. Despite the extensive research, its pathophysiology remains largely unelucidated. Currently, more attention is being given to the disease’s vascular and inflammatory aspects. In this context, the renin-angiotensin system (RAS) emerges as a credible player in AD pathogenesis. RAS has multiple physiological functions, conducted by its two opposing axes: the classical, led by Angiotensin II (Ang II), and the alternative, driven by Angiotensin-(1-7) [Ang-(1-7)]. These peptides were shown to interact with AD pathology in animal studies, but evidence from humans is scarce. Only 20 studies dosed RAS molecules in AD patients’ bloodstream, none of which assessed both axes simultaneously. Therefore, we conducted a cross-sectional, case-control exploratory study to compare plasma levels of Ang II and Ang-(1-7) in AD patients vs. age-matched controls. Within each group, we searched for correlations between RAS biomarkers and measures from magnetic resonance imaging (MRI). Methods: We evaluated patients with AD (n=14) and aged-matched controls (n=14). Plasma Ang II and Ang-(1-7) were dosed using ELISA. Brain MRI was performed in a 3 Tesla scan, and a three-dimensional T1-weighted volumetric sequence was obtained. Images were then processed by FreeSurfer to calculate: 1) white matter hypointensities (WMH) volume; 2) volumes of hippocampus, medial temporal cortex, and precuneus. Statistical analyses used non-parametrical tests (Mann-Whitney and Spearman) Results: Ang-(1-7) levels in plasma were significantly lower in the AD patients than in controls [median (25th – 75th percentiles)]: AD [101.5 (62.43 – 126.4)] vs. controls [209.3 (72 – 419.1)], p = 0.014 (Fig. 1A). There was no significant difference in circulating Ang II. In the AD patients, but not in controls, there was a positive and significant correlation between Ang-(1-7) values and WMH volumes in AD (Spearman’s rho =0.56, p = 0.038). Ang-(1-7) did not correlate with cortical volumes in AD or in controls. Ang II did not correlate with any MRI variable in none of the groups. Conclusions: If confirmed, our results strengthen the hypothesis that RAS alternative axis is downregulated in AD, and points to a possible interaction between Ang-(1-7) and cerebrovascular lesions in AD.